Strategi Pengembangan Profesionalisme Guru Madrasah Diniyah di Indonesia - Moh Lukmanul Hakim (Jurnal Ilmiah Iqra', 2021)
Strategy for Professional Development of Early Madrasah Teachers in Indonesia. This study aims to determine the patterns and strategies for the professional development of madrasah diniyah teachers in Indonesia. The method used in this research is library research with an explanatory approach. Collecting data using relevant research and factual data. The results of the study indicate that there are several shortcomings of the professional development of madrasah diniyah teachers, namely static learning patterns and conventional delivery of material so that it is necessary to update the strategies carried out by madrasas to improve quality through three innovative programs, namely pre-service education, in-service education, and in-service training